A MICROMORPHOLOGICAL STUDY OF SOME GENERA OF THE PAPILIONOIDEAE SUBFAMILY IN CENTRAL AND NORTHERN IRAQ - A. H. Abdulmajeed; N. M. Muhammad (مجلة الأنبار للعلوم الزراعية)
This research involved a micro-morphological pollen study on 23 wild plant species belonging to six genera of the Papilionoideae subfamily growing in the central and northern districts of Iraq. These are Astragalus, Lathyrus, Medicago, Pisum, Trifolium, and Vicia. The samples were collected from February 2022 to June 2023. Altogether 34 field tours were made for conducting a comprehensive survey and to examine preserved herbarium specimen samples from the National Herbarium of Iraq and various universities. Pollen grains were examined for the arrangement of genera using a light microscope (LM 1000X) and a field-emission scanning electron microscope (FESEM). Diagnostic characteristics studied included the grain axis, apertures, E/P ratio, size, pollen grain shape, and surface ornamentation. The results show that the pollen grain were small-to-medium sized, tricolporate, isopolar, prolate, and spheroidal-to-subspheroidal. In addition, the surface ornamentation showed reticulate perforates, subperforate reticulate striates, reticulate sub-striate ornamentation, and reticulate perforate-striates. In conclusion, this study presents some morphological characteristics of pollen grains from the Papilionoideae subfamily in which LM (1000X) and FESEM were found to be useful and reliable tools in determining the importance of this classification in achieving historical knowledge of these seeds